2012
DOI: 10.1007/s12471-012-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and weekly variation and the influence of environmental variables in acute myocardial infarction

Abstract: Incidence of AMI shows a circadian pattern with an increase in occurrence during daylight. AMI occurs equally on each day of the week and no relation was found between environmental variables and the occurrence of AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Environmental variables such as the sunlight have also proved to play an important role in the onset of MI in both hemispheres [20]. Previous studies have suggested an increased onset of MI during daylight hours [23], during periods of short sunlight duration [24] and a “summer shift” with decreased difference between numbers of diurnal and nocturnal MIs during the summer [20]. Air temperature, low atmospheric air pressure and high wind velocity have also been demonstrated to have a strong association with MI [24].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental variables such as the sunlight have also proved to play an important role in the onset of MI in both hemispheres [20]. Previous studies have suggested an increased onset of MI during daylight hours [23], during periods of short sunlight duration [24] and a “summer shift” with decreased difference between numbers of diurnal and nocturnal MIs during the summer [20]. Air temperature, low atmospheric air pressure and high wind velocity have also been demonstrated to have a strong association with MI [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Danet et al reported a 12% increase in the incidence of acute heart disease for every 10 mbar drop in atmospheric pressure below 1016 mbar and an 11% increase for every 10 mbar rise above this threshold [ 10 ]. However, several studies did not find a significant relationship between the occurrence of AMI and air pressure [ 31 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal Vasconcelos et al [ 47 ] also reported a negative correlation, although they used various indices rather than individual meteorological variables. On the other hand, Wijnbergen et al from The Netherlands [ 48 ] and Goerre et al from Switzerland [ 35 ] report that incidences of AMI do not statistically significantly differ between colder days and warmer days. Similarly, a study of hospitals in a Turkish city and patients over the age of 65 did not confirm any connection between incidence and low temperatures [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The few European studies that included pressure in their analysis found contradicting results. Some did not find any relation between pressure and the incidence of AMI [ 43 , 48 , 51 , 52 ] or the relationship was not statistically significant [ 52 ]. Others describe either a positive correlation [ 35 , 36 ] or, as in our study, a negative correlation [ 36 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation